History of foot ulcers increases mortality among patients with diabetes in Northern Thailand - Junrungsee S. (2017)
Aims Studies within the Caucasian population with diabetes showed an increased mortality in patients with diabetic foot ulcers. However, there were no such studies based on Asian populations. We therefore designed our study on the association of foot ulcer with mortality within the Asian population. Methods Ninety-seven Asian individuals with diabetes who had previously participated in the 'Multidisciplinary Diabetic Foot Protocol' between 2005 and 2007 at our centre were followed up in 2010 to ascertain their mortality rate. Cox proportional-hazard regression analyses were used to estimate hazard ratios. Results Forty-seven patients had a history of foot ulcer (group1), while 50 had none (group2). The mean follow-up was 43.74months. Twenty-one patients died during this period (21.65%). The mortality rates in group1 and group2 were 15 (31.92%) and six (12.00%), respectively. Patients with a history of foot ulcer had higher mortality rates than those without (hazard ratio3.51, 95%CI 1.03-11.96, P=0.04). Conclusions Our study showed that history of foot ulcer increased mortality. This association appeared to be stronger in younger Asian patients than those in the Caucasian populations. © 2011 The Authors. Diabetic Medicine © 2011 Diabetes UK.